Is math real? : how simple questions lead us to mathematics' deepest truths - Cheng, Eugenia (London: Profile Books Ltd., 2024)
"Where does math come from? From a textbook? From rules? From deduction? From logic? Not really, Eugenia Cheng writes in Is Math Real?: it comes from curiosity, from instinctive human curiosity, "from people not being satisfied with answers and always wanting to understand more." And most importantly, she says, "it comes from questions": not from answering them, but from posing them. Nothing could seem more at odds from the way most of us were taught math: a rigid and autocratic model which taught us to follow specific steps to reach specific answers. Instead of encouraging a child who asks why 1+1 is 2, our methods of education force them to accept it. Instead of exploring why we multiply before we add, a textbook says, just to get on with the order of operations. Indeed, the point is usually just about getting the right answer, and those that are good at that, become "good at math" while those who question, are not. And that's terrible: These very same questions, as Cheng shows, aren't simply annoying questions coming from people who just don't "get it" and so can't do math. Rather, they are what drives mathematical research and push the boundaries in our understanding of all things. Legitimizing those questions, she invites everyone in, whether they think they are good at math or not. And by highlighting the development of mathematics outside Europe, Cheng shows that-western chauvinism notwithstanding--that math can be for anyone who wishes to do it, and how much we gain when anyone can"--
Where maths comes from -- How maths works -- Why we do math -- What makes maths good -- Letter -- Formulae -- Pictures -- Stories.
"Published in 2023 in the UK by Profile Books."
Includes bibliographical references and index.
Keywords: Mathematics -- Philosophy; Mathematics -- Popular works